Rat Brain Normalization Templates for Robust Regional Analysis of [C]ABP688 Positron Emission Tomography/Computed Tomography - Jeroen Verhaeghe; Leonie Wyffels; Tine Wyckhuys; Sigrid Stroobants; Steven Staelens (Molecular Imaging)
A methodology to generate rat brain templates for spatial normalization of positron emission tomographic (PET)/computed tomographic (CT) images is described and applied to generate three different templates for imaging of [ 11 C]ABP688, a PET ligand binding to the metabotropic glutamate 5 receptor. The templates are based on functional (PET), structural (CT), and combined PET and CT information, respectively. The templates are created from a test–retest study under normal conditions and are used to assess the different templates by using them in the analysis pipeline of a test–retest and a blocking experiment. The resulting average nondisplaceable binding potentials (BP ND ) show significant (analysis of variance, p < .05) and substantial (up to 23%) differences between the different approaches in several brain regions. The highest BP ND values in receptor-rich regions are obtained using the PET-based approach. This approach also had the smallest variability in all tested regions (standard error of measurement of 9% versus 14% [PET/CT] and 20% [CT]). All approaches showed similar relative changes in BP ND values with increased blocking. Taken together, these results suggest that the use of the tracer-specific PET-based template outperforms the other approaches with the performance of the combined PET/CT template between those of the PET and the tracer-independent CT template.